Impact of Polycyclic Aromatic Hydrocarbons on the Environment and Human Health: Evidence Retrieved from Biomonitoring Studies - Joana Teixeira; Cristina Delerue-Matos; Simone Morais; Marta Oliveira (Proceedings, 2024)
The presence of polycyclic aromatic hydrocarbons (PAHs) in different environmental matrices has significant repercussions on ecosystems and human health [...]